Proteins and Amino Acids Treated with Atmospheric Plasma Show Significantly Increased Bioavailability in Humans. (September 2020) - Sharp, Matthew H; Stefan, Matthew W; Gheith, Raad H; Reber, Dallen D; Ottinger, Charlie R; Wilson, Jacob M; Lowery, Ryan P
Background: Muscle mass is an important determinant of metabolic health and physical function. It has previously been demonstrated that the postprandial rise in circulating essential amino acids acts as the main stimulus for muscle protein synthesis (MPS). The current study investigated the postprandial plasma essential amino acid (EAA) and branched-chain amino acid (BCAA) responses of (1) Hydrolyzed whey protein isolate (HWPI) compared to plasma treated non-hydrolyzed whey protein isolate (PT-NHWPI), (2) standard branch-chain amino acids (S-BCAA) compared to plasma treated branch-chained amino acids (PT-BCAA), (3) standard pea protein (S-PP), compared to plasma treated pea protein (PT-PP), and (4) HWPI compared to PT-PP. Methods: Ten subjects (24.6 ± 5.3 years; 178.8 ± 8.1 cm; 78.6 ± 10.1 kg) participated in a double-blind, randomized, crossover trial comparing four separate protein conditions (HWPI, PT-NHWPI, S-PP, PT-PP). A separate cohort of ten subjects (26.4 ± 7.4 years; 178.8 ± 5.9 cm; 85 ± 12.3 kg) participated in a double-blind randomized, crossover trial comparing two branch-chain amino acid conditions: S-BCAA and PT-BCAA. All conditions were administered following a 7-day washout. Plasma EAA and BCAA concentrations were assessed from blood donated by subjects at pre-consumption, 30-, 60-, 90-, 120-, and 180 minutes post-consumption. Results: Blood plasma levels of total EAA and BCAA concentration were significantly greater in all treated conditions at 30-, 60-, 90-, and 120 minutes post consumption ( P  < .05). There were no differences between PT-PP and HWPI. Discussion: All proteins significantly elevated EAAs, and BCAAs from basal levels. However, we conclude that the consumption of the treated proteins significantly raises blood levels of EAAs, and BCAAs to a greater extent across multiple dairy, vegan, and isolated BCAA conditions. Moreover, atmospheric plasma treatment of a vegan protein source makes its amino acid response similar to whey. Thus, protein supplementation with that has undergone Ingredient Optimized® atmospheric plasma treatment technology may be highly beneficial for improving the blood plasma amino acid response.